Combination of diagnostic laparoscopy and intraoperative indocyanine green fluorescence angiography for the early detection of intestinal ischemia not detectable at CT scan. (2016) - Alemanno, Giovanni; Somigli, Riccardo; Prosperi, Paolo; Bergamini, Carlo; Maltinti, Gherardo; Giordano, Alessio; Valeri, Andrea
Highlights: The recognition of intestinal ischemia often occurs too late due to the presence of unspecific symptoms and lack of reliable exams. The combination of laparoscopy and UV light and fluorescein dye should be considered as an invaluable procedure for the early diagnosis of acute bowel ischemia. ICG can intraoperatively provide more useful information than conventional clinical assessment, mostly in case of a non-diagnostic CT scan. Abstract: Introduction: Acute mesenteric ischemia is the most severe gastrointestinal complication of acute aortic dissection. The timing of diagnosis is of major importance, in fact the recognition of acute mesenteric ischemia often occurs too late due to the presence of unspecific symptoms and lack of reliable exams. Recently, indocyanine green fluorescence angiography has been adopted in order to measure blood perfusion and microcirculation. Presentation of case: We decided to perform a diagnostic laparoscopy with the support of intra-operative near-infrared indocyanine green fluorescence angiography, in order to detect an initial intestinal ischemia in a 68-year-old patient previously treated with a TEVAR procedure for a type-B aortic dissection. The fluorescence system demonstrated an hypoperfused area in the ascending colon, therefore an ileocholic resection was thus performed. Opening the operatory specimen, the mucosa of the colon appeared totally ischemic, whilst the serosa was normal. Discussion: When ischemia occurs, the oxygen supply is interrupted, hence the necrosis of the enteral mucosa occurs within 3 h, whilst the necrosis of the full thickness of the bowel wall occurs within 6 h. A diagnosis during these "golden hours" is of major importance for a successful treatment. Conclusion: The combination of laparoscopy and UV light and fluorescein dye should be considered as an invaluable diagnostic procedure for the diagnosis of early stage acute bowel ischemia which is not visible at instrumental examinations nor with diagnostic laparoscopy.